Szkolny kontekst psychologii pozytywnej. Studium empiryczne - Czerniga-Puk, Paulina; Juńczyk, Tomasz (Wydawnictwo Naukowe UAM, 2015)
Previous research on the effects of techniques of positive psychology on students’ psychological welfare and school grades bring very promising results. The authors decided to test the hypothesis of the impact of students’ attributional style on their grades in mathematics. For this purpose, a pilot study was conducted on a group of 68 students of lower secondary school. The results partially support the hypotheses tested. The article also provides a catalog of practical methodical recommendations for teachers. These recommendations have been implemented practically in educational context and its effectiveness have been proven.
Educational Context of Positive Psychology. An Empirical Study
Keywords: positive psychology; attributional styles; lower secondary school